Food Insecurity and Chronic Diseases among Native Hawaiians and Pacific Islanders in the US: Results of a Population-based Survey. Issue 1 (2nd January 2022) - Long, Christopher R.; Narcisse, Marie-Rachelle; Bailey, Mary M.; Rowland, Brett; English, Emily; McElfish, Pearl A.
ABSTRACT: Data from the 2014 Native Hawaiian and Pacific Islander (NHPI) National Health Interview Survey were used to examine associations between food security and individual chronic diseases, total number of chronic diseases, and general health status among 637 NHPI adults with income below 200% federal poverty level. Very low food security was associated with hypertension, diabetes, and asthma. Very low food security and marginal food security were associated with having any chronic disease and with having a higher number of chronic diseases. Risk for food insecurity increased as health status decreased. These associations had not previously been documented for NHPI.